Statistical analysis of the participation of multiple disadvantaged students in the Integrative Pedagogical System - Híves, Tamás (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The paper analyses some features of the IPS program, supporting disadvantaged students. The analysis compares the data of participating students to disadvantaged, low-achiever students, those who play truant, and Roma population. The analysis examined the connections with the help of statistical and regional methods, e.g. maps, tables. With the help of these methods – emphasizing regional disparities - differences can be pointed out between the participants of the program and those groups who are in need of help. By exploring regional disparities disadvantaged situations can be treated more effectively. With the method of regional geographic analysis and maps it becomes obvious even for non-professionals that where are the geographical areas, where the support of disadvantaged students were successful and which are the areas where problems still can be found.